THE EFFECTIVENESS OF ONLINE TICKET MANAGEMENT BY VOLUNTEER IN GREBEG SURO 2018 AND REYOG PONOROGO NATIONAL FESTIVAL XXV - Hilman, Yusuf; Nugroho, Irfan (CosmoGov: Jurnal Ilmu Pemerintahan, 2020)
Reyog Ponorogo National Festival (FNRP) is a national-level tourism agenda that is annually held in Ponorogo Regency, within the past 30 years, the Festival has begun to be improved in the right direction, deficiencies that have emerged, was tried to inventory and then improved, right at the holding of the Reyog Ponorogo National Festival (FNRP) in 2018 the committee developed a Voluntary Volunteer idea where volunteers were tasked with helping the agenda run smoothly, one of which was managing online ticket sales. This research used descriptive qualitative type, with the model of determining informants using purposive sampling, and data validity testing through triangulation. Online ticket management by Volunteer Grebeg Suro in organizing Grebeg Suro 2018 and the Reyog Ponorogo National Festival XXV could be concluded as effectively way. This was proofen from the respondents assessment of the results of interviews that had all been expressed positive attitudes. Online tickets for Grebeg Suro and Reyog Ponorogo National Festival were considered to be very effective in organizing Grebeg Suro and Reyog Ponorogo National Festival events. Some assessment indicators were based on the time spent, the convenience provided, and the education provided to the community. gb777